2023
DOI: 10.1186/s12877-023-04301-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing shared decision-making in long-term care facilities

Da Eun Kim,
Min Jung Kim

Abstract: Background Shared decision-making, a communicative process to reach decisions based on informed preferences, evidence, and co-created goals, improves care satisfaction and patients’ quality of life. However, shared decision-making has not been widely implemented in long-term care facilities, and few studies have examined how to promote the shared decision-making practice. This study aimed to identify the influencing factors of shared decision-making based on the Person-centered Practice Framewo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The aim of medical aesthetic intervention is to enhance an individual's overall appearance and well-being, with procedures typically driven by the patient's desires rather than medical necessity, and the subjective nature of beauty standards, potential psychological implications of aesthetic procedures, and ethical considerations could also influence the decision-making dynamics, all of which demonstrates the significant value of SDM for the selection of treatment options in medical aesthetics. [9][10][11] However, evidence demonstrating whether SDM is universally applied or not is not yet understood and studied in China. 12,13 Previous studies indicated that Chinese physicians perceived SDM with high willingness (78.38%) based on the discrete-choice experiment (DCE) survey and the SDM questionnaire physician version (SDM-Q-Doc) survey.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of medical aesthetic intervention is to enhance an individual's overall appearance and well-being, with procedures typically driven by the patient's desires rather than medical necessity, and the subjective nature of beauty standards, potential psychological implications of aesthetic procedures, and ethical considerations could also influence the decision-making dynamics, all of which demonstrates the significant value of SDM for the selection of treatment options in medical aesthetics. [9][10][11] However, evidence demonstrating whether SDM is universally applied or not is not yet understood and studied in China. 12,13 Previous studies indicated that Chinese physicians perceived SDM with high willingness (78.38%) based on the discrete-choice experiment (DCE) survey and the SDM questionnaire physician version (SDM-Q-Doc) survey.…”
Section: Introductionmentioning
confidence: 99%